2018
DOI: 10.1097/ico.0000000000001507
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Diagnostic Accuracy of Laser-Scanning In Vivo Confocal Microscopy for Acanthamoeba Keratitis

Abstract: IVCM has a moderate sensitivity and a high specificity for diagnosis of AK. Although clinical parameters do not affect this diagnostic accuracy, a higher sensitivity is seen when images are interpreted by experienced observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…IVCM allows the direct observation of fungal hyphae, spores, and acanthamoeba cysts in living corneas. 37 , 38 Previous clinical studies have shown that IVCM has good sensitivity and specificity in the diagnosis of fungal and acanthamoeba infection keratitis. IVCM may be missed or misdiagnosed in many cases, including corneal edema, excess necrotic tissue, or fungal hyphae in the deep stroma or on the endothelium surface.…”
Section: Discussionmentioning
confidence: 99%
“…IVCM allows the direct observation of fungal hyphae, spores, and acanthamoeba cysts in living corneas. 37 , 38 Previous clinical studies have shown that IVCM has good sensitivity and specificity in the diagnosis of fungal and acanthamoeba infection keratitis. IVCM may be missed or misdiagnosed in many cases, including corneal edema, excess necrotic tissue, or fungal hyphae in the deep stroma or on the endothelium surface.…”
Section: Discussionmentioning
confidence: 99%
“…In-vivo confocal microscopy is more sensitive than cultures and PCR for fungal and Acanthamoeba infections, but results are highly dependent on user experience level [39][40][41]. Anterior segment optical coherence tomography is another potentially useful modality in distinguishing fungal from bacterial and viral infection or in performing corneal endothelial biopsies [42][43][44].…”
Section: Diagnosticsmentioning
confidence: 99%
“…The effects of contact lenses on the eyes were evaluated with CSLM. Contact lens biocompatibility, its effects on cornea, limbal stem cells or conjunctiva, early diagnosis of devastating infections such as acanthamoeba keratitis are investigated by CSLM [35][36][37][38].…”
Section: Contact Lensmentioning
confidence: 99%
“…Its incidence is on the rise because of the increasing usage of contact lenses. The diagnose of acanthamoeba keratitis is essential as its devastating nature, and CSLM can be used as an adjunct modality to the clinical data for diagnosing acanthamoeba keratitis [38].…”
Section: Contact Lensmentioning
confidence: 99%